Bifurcation conditions for the solutions of weakly perturbed boundary-value problems for operator equations in Banach spaces - Zhuravlev, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain bifurcation conditions for the solutions of weakly perturbed boundary-value problems for operator equations in Banach spaces from the point ε = 0. A convergent iterative procedure is proposed for the construction of solutions as parts of series in powers of ε with pole at the point ε = 0.